2023
DOI: 10.1111/ijfs.16261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postharvest processing on aroma formation in roasted coffee – a review

Abstract: Postharvest processing of coffee cherries significantly influences sensory characteristics and commercial values. Aroma is one of the critical elements in product qualification and differentiation of coffees from different origins, roasting levels and brewing methods. Except for primary coffee volatile organic compounds (VOCs) (furans and pyrazines), which are generated during postharvest processing (dry, honey, wet processing and roasting), aldehydes, ketones, phenols, sulphur compounds and others could also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 124 publications
1
10
0
1
Order By: Relevance
“…Some of them are sulfur compounds, such as sulfides and thiols, particularly 2-furfurylthiol; Strecker aldehydes, such as methylpropanal, 2-methylbutanal, and 3-methylbutana; and α-Dicarbonyls such as 2,3-butanedione and 2,3-pentanedione [17]. Includes pyrazines, furans and derivatives, ketones, phenolic compounds [18]. Also includes, terpenes, pyrazole, pyridines, acids, pyrroles, and alcohols [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are sulfur compounds, such as sulfides and thiols, particularly 2-furfurylthiol; Strecker aldehydes, such as methylpropanal, 2-methylbutanal, and 3-methylbutana; and α-Dicarbonyls such as 2,3-butanedione and 2,3-pentanedione [17]. Includes pyrazines, furans and derivatives, ketones, phenolic compounds [18]. Also includes, terpenes, pyrazole, pyridines, acids, pyrroles, and alcohols [19].…”
Section: Resultsmentioning
confidence: 99%
“…Higher roasting time provides elevated weight loss due to the evaporation of moisture from the grains [20][21][22]. Four different roasting time (16,18, 20 and 22 minutes) and two particle sizes (medium and fine) were analyzed for the preference of coffee consumers from Paraná state, Brazil. These authors reported that coffee beans roasted for 20 minutes was preferred, and particle size did not affect the consumers choice [20], and the weight loss was, respectively, 10.60 %, 11.25 %, 18.65 % and 22.78 % for 16, 18, 20 and 22 minutes of roasting process.…”
Section: Resultsmentioning
confidence: 99%
“…For all the identified pyrazines, sucrose is the main carbohydrate precursor. The side products of the Strecker degradation of amino acids can release aroma-active volatile aldehydes, which are crucial for the flavor of coffee [ 43 ]. In addition, the fragmentation of the side chains may lead to the formation of pyrazines.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it might be supposed that the COC residues of the pulped-natural processed PMT-PDD contain residual sugars that lead to reduced sugar molecules during thermal treatment. It was shown by Cao et al [ 44 ] and Gancarz et al [ 45 ] that the Maillard reaction, starting during coffee roasting at approx. 140 °C, can create VOC with an associated non-enzymatic browning of the biomass.…”
Section: Resultsmentioning
confidence: 99%